Ответы и объяснения

2013-01-24T01:46:16+00:00

tg^{2}(3x)- 4sin^{2}(3x) = 0\\ \frac{sin^{2}(3x) - 4sin^{2}(3x)\cdot cos^{2}(3x)}{cos^{2}(3x)} = 0\\ \frac{sin^{2}(3x) - 4sin^{2}(3x)\cdot (1 - sin^{2}(3x))}{cos^{2}(3x)} = 0\\ \frac{-3sin^{2}(3x) + 4sin^{4}(3x)}{cos^{2}(3x)} = 0\\ \begin{cases} 2sin^{2}(3x) - \sqrt{3}sin(3x) = 0\\2sin^{2}(3x) + \sqrt{3}sin(3x) = 0\\cosx \neq 0 \end{cases} \begin{cases} x = (-1)^{n}\frac{\pi}{9} + \frac{\pi}{3}n\\x =(-1)^{z + 1}\frac{\pi}{9} + \frac{\pi}{3}z \\x \neq +-\frac{\pi}{2} + 2\pi k \end{cases}

Ну выборку уже сама сделай... и все конец